2020
DOI: 10.1101/2020.03.20.001081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pyronaridine Tetraphosphate Efficacy Against Ebola Virus Infection in Guinea Pig

Abstract: 31The recent outbreaks of the Ebola virus (EBOV) in Africa have brought global visibility to 32 the shortage of available therapeutic options to treat patients infected with this or closely 33 related viruses. We have recently computationally identified three molecules which have 34 all demonstrated statistically significant efficacy in the mouse model of infection with 35 mouse adapted Ebola virus (ma-EBOV). One of these molecules is the antimalarial 36 pyronaridine tetraphosphate (IC 50 range of 0.82-1.30 µM… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…A recent species comparison of metabolism of tilorone demonstrated N-deethylation and mono-oxygenation was higher in guinea pig relative to both mouse and human (33). The species-liver microsome stability relationship increased in the order of guinea pig, non-human primate, mouse, followed by human (33). The differences in metabolic stability between species could also account for any differences in efficacy observed between the mouse and guinea pig models of EBOV treated with tilorone.…”
Section: Species Differences In Metabolismmentioning
confidence: 99%
“…A recent species comparison of metabolism of tilorone demonstrated N-deethylation and mono-oxygenation was higher in guinea pig relative to both mouse and human (33). The species-liver microsome stability relationship increased in the order of guinea pig, non-human primate, mouse, followed by human (33). The differences in metabolic stability between species could also account for any differences in efficacy observed between the mouse and guinea pig models of EBOV treated with tilorone.…”
Section: Species Differences In Metabolismmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 28, 2020. ; https://doi.org/10.1101/2020.05.26.118182 doi: bioRxiv preprint Prior work on pyronaridine has demonstrated that it has promising in vitro activity against EBOV as well as excellent in vitro absorption, distribution, metabolism and excretion (ADME) properties and a very long half-life across mice and humans (21). It also has statistically significant in vivo efficacy in mice and guinea pigs infected with EBOV (24). While the mechanism to date was unclear, it has been shown to inhibit lysostracker suggesting a lysosomotropic effect (25).…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…It has excellent in vitro ADME properties and was recently demonstrated to have potent in vitro inhibition of EBOV as well as efficacy in mouse infected with EBOV (22). Interestingly this molecule did not demonstrate efficacy in the guinea pig EBOV model likely due to the significant species differences in metabolism when compared to mouse (24). Tilorone has also demonstrated in vitro inhibition of MERS (26) and is under evaluation as a potential treatment for other coronaviruses such as SARS-CoV-2 (23) and has shown a low M IC 50 (27).…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation